2007
DOI: 10.1002/path.2227
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles in HPV‐infected head and neck cancer

Abstract: Epidemiological and laboratory evidence indicate that, in addition to tobacco and alcohol, human papillomaviruses (HPV) play an important aetiological role in a subset of head and neck squamous cell carcinoma (HNSCC). To evaluate the molecular pathogenesis of HPV-infected HNSCC, we compared gene expression patterns between HPV-positive and -negative HNSCC tumours using cDNA microarrays. Tumour tissue was collected from 42 histologically confirmed HNSCC patients from an inner-city area of New York. Total DNA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 63 publications
(86 reference statements)
5
79
0
2
Order By: Relevance
“…For example, OSCC has a much greater propensity for spread with poor outcomes compared with OPSCC (Franceschi et al, 1993;Dobrossy, 2005;Timar et al, 2005;Yu et al, 2008). This site specificity is also reflected by the presence of HPV, which is known to have a distinct gene expression profile (Ragin et al, 2006;Slebos et al, 2006;Schlecht et al, 2007;Shaw et al, 2010;van Hooff et al, 2012b). We established the HPV status of the cohort using a gold standard test and identified that the presence of HPV was unlikely to be a confounding variable in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, OSCC has a much greater propensity for spread with poor outcomes compared with OPSCC (Franceschi et al, 1993;Dobrossy, 2005;Timar et al, 2005;Yu et al, 2008). This site specificity is also reflected by the presence of HPV, which is known to have a distinct gene expression profile (Ragin et al, 2006;Slebos et al, 2006;Schlecht et al, 2007;Shaw et al, 2010;van Hooff et al, 2012b). We established the HPV status of the cohort using a gold standard test and identified that the presence of HPV was unlikely to be a confounding variable in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, these technologies have had little impact on standard methods for diagnosis and treatment of HNSCC and many other types of cancer with one or more known mutational or copy number drivers. Despite extensive literature of differential gene expression profiles, mutations and copy number abnormalities in head and neck tumors that could potentially impact future clinical applications, little other than HPV status is done routinely upon diagnosis [7,10,11,13,15,24,32,[35][36][37][38][39][40][41][42][43][44][45][46][47]. A main factor contributing to this lack of progress is that no clear directives or actionable guidelines have been adopted for molecularly profiling HNSCCs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown that HPV testing by PCR alone is not sufficient for diagnosis of OPSCC [11,12]. Numerous gene expression studies have been previously used to categorize HPV-positive versus negative OPSCC, and despite numerous reports of the potential clinical benefit of such testing, none of these signatures have been adopted as a routine diagnostic for OPSCC [13].…”
Section: Introductionmentioning
confidence: 99%
“…21 In addition, studies investigating gene expression in HPV-positive and HPV-negative HNSCC show distinct transcriptomic patterns, which might be partly due to viral E6-and E7-mediated alterations in the genome and epigenome. [22][23][24][25] One group of different expressed genes is that of DNA methyltransferases, involved in regulation of DNA methylation. 26,27 Differences in methylation profiles between HPV-positive and HPV-negative OPSCC have been explored in many studies, though most promoter methylation studies have evaluated only a limited number of genes and did not focus on solely the oropharynx.…”
Section: Reviewmentioning
confidence: 99%